Table of Contents, Vol. 14, Issue 2, Reckoning - M. Therese Lysaught (Journal of Moral Theology, 2025)
The church in the US faces just such a moment of reckoning. From the centuries of collusion by in the idolatries undergirding the sacrifice and exploitation of vast peoples to the twisted account of ‘Christian nationalism’ that is the current apotheosis of this history, the church is finding itself called to give an account of itself to itself, to the wider public, and to God. One piece of that accounting is the role Christian theology has played in the church’s failure. The articles in this issue of the _Journal of Moral Theology_ undertake this work, while also lifting up possibilities for the beginnings of repair.